Optimizing dual modal biometric authentication: hybrid HPO-ANFIS and HPO-CNN framework - Sandeep Pratap Singh; Shamik Tiwari (Institute of Advanced Engineering and Science, 2024)
In the realm of secure data access, biometric authentication frameworks are vital. This work proposes a hybrid model, with a 90% confidence interval, that combines